Washing-free chromium-free antioxidant liquid for copper foil of lithium ion battery as well as preparation method and use method of washing-free chromium-free antioxidant liquid

By developing a water-free chromium-free antioxidant liquid, using components such as corrosion inhibitors, film-forming additives, sealing agents and dispersants to form an antioxidant film without water washing, solving the environmental pollution and waste of water resources caused by the use of chromium-containing liquids in the prior art, and achieving efficient and environmentally friendly copper foil surface treatment of lithium-ion batteries.

CN119736616APending Publication Date: 2025-04-01HARBIN INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411949546.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The antioxidant treatment of copper foils in existing lithium-ion batteries requires the use of chromium-containing passivation liquid, which leads to environmental pollution and waste of water resources. At the same time, these liquids require water washing steps during use, which can easily lead to appearance defects on the surface of the copper foil.

Method used

A water-free chromium-free antioxidant liquid is developed to form an antioxidant film without washing to protect the surface of the copper foil by using components such as corrosion inhibitors, film-forming additives, sealing agents and dispersants.

Benefits of technology

A uniform and dense protective film is formed on the surface of the copper foil of lithium-ion batteries, which significantly improves its oxidation and corrosion resistance, avoids waste of water resources and environmental pollution in the washing step, and does not affect the conductive properties and wettability of the copper foil.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736616A_ABST
    Figure CN119736616A_ABST
Patent Text Reader

Abstract

The invention discloses washing-free chromium-free antioxidant liquid for a lithium ion battery copper foil and a preparation method and a use method thereof, and belongs to the technical field of metal surface treatment. In order to develop a surface treatment process of a lithium ion battery copper foil which is green, environment-friendly and excellent in performance, the lithium ion battery copper foil comprises the following components: 0.1-10g / L of a corrosion inhibitor, 0.1-10g / L of a coalescing agent, 0.1-10mL / L of a sealing agent, 0.1-10mL / L of a dispersing agent and the balance of deionized water, then sodium hydroxide and formic acid are used for adjusting the pH value of a solution to be 4-6, and the lithium ion battery copper foil is prepared. And the deionized water is used for fixing the volume to obtain the washing-free chromium-free antioxidant liquid for the lithium ion battery copper foil. A layer of passivation film with excellent oxidation resistance and corrosion resistance can be obtained on the surface of the copper foil for the lithium ion battery, the copper foil can be protected from discoloring after being baked at 140 DEG C for 15 min, meanwhile, the conductivity and wettability of the passivated copper foil are not affected, and the requirements of the copper foil for the lithium ion battery are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal surface treatment, and specifically relates to a water-free, chromium-free antioxidant liquid for lithium ion battery copper foil, a preparation method and a use method thereof. Background Art

[0002] In order to obtain lithium-ion batteries with higher battery capacity, people have been committed to developing new battery materials to support the research and development of high energy density and lightweight lithium-ion batteries. Copper foil is the negative electrode current collector of lithium-ion batteries. By thinning the copper foil, lithium-ion batteries can be lightweight and energy density can be improved. Copper foil can be divided into rolled copper foil, electrolytic copper foil and composite copper foil according to the preparation process. Due to the limitations of process conditions and costs, the thickness of rolled copper foil is limited to about 10-12μm. Electrolytic copper foil and composite copper foil prepared by electrodeposition process can reach 4.5-6μm or even thinner. Therefore, using thinner electrolytic copper foil current collector can significantly reduce the weight of LIB and improve its energy density. Electrolytic copper foil is prone to corrosion and discoloration in the humid environment prepared by copper sulfate plating solution, resulting in poor conductivity and surface wettability. In addition, as an important component of lithium-ion battery current collector, electrolytic copper foil is easily corroded by electrolyte when exposed to electrolyte for a long time, thereby contaminating the electrolyte and even destroying the anode structure, affecting the internal resistance, battery capacity, cycle life and safety of lithium-ion batteries. Therefore, electrolytic copper foil needs to go through post-processing steps during the production process to ensure higher anti-oxidation and anti-corrosion properties.

[0003] At present, the antioxidant treatment of copper foil for lithium-ion batteries mainly relies on a passivation solution containing hexavalent chromium. This method has the advantages of simple process and low cost, and can effectively improve the antioxidant properties of copper foil. However, due to the significant harm of hexavalent chromium to the environment, its use is gradually being restricted. As an alternative, a passivation solution containing trivalent chromium is widely used. Although its toxicity is lower than that of hexavalent chromium, it still has a certain impact on the environment. In addition, the use of chromium-containing passivation solution usually requires a water-free washing process, which can easily lead to water spots on the surface of the copper foil, and then cause appearance defects such as color difference and wrinkles, affecting its use. Therefore, it is urgent to develop a water-free, chromium-free antioxidant solution for lithium-ion battery copper foil.

[0004] The invention application with the publication number CN119082719A discloses an antioxidant surface treatment agent for copper foil and its preparation method and use method. The antioxidant surface treatment agent for copper foil is composed of the following components in mass percentage: 0.5-5% silane coupling agent; 0.1-5.0% silicone resin; 0.1-2.0% benzotriazole; 0.5-5% ammonia water; 2-5% ethanol; the rest is deionized water. Although the antioxidant surface treatment agent for copper foil provided by the invention does not need to be powered on during use, and the passivation method is spraying and then drying, and does not need water washing, the antioxidant surface treatment agent contains a high concentration of silane coupling agent and silicone resin. The film layer formed by these two substances on the surface of copper foil will affect the conductive properties of copper foil, and is not suitable for lithium ion battery copper foil with high conductivity requirements.

[0005] The invention application with publication number CN118727085A discloses an environmentally friendly antioxidant additive for copper foil and its preparation method. The environmentally friendly antioxidant additive for copper foil includes the following concentration components: L-methionine 40-80g / L, 3-amino-1,2-propylene glycol 20-40g / L, ethyl carbamate 2-4g / L, 2,6-dichloropyridine 2-4g / L, and the rest is deionized water. Although the antioxidant will not significantly increase the resistance of the copper foil while ensuring the excellent antioxidant and corrosion resistance of the copper foil, the antioxidant still requires a water washing step during use. The system uses a relatively high concentration of amino-containing substances, which will produce a large amount of nitrogen-containing wastewater during the water washing process and will also cause pollution to the environment. Summary of the invention

[0006] The problem to be solved by the present invention is to develop a green, environmentally friendly, and excellent performance lithium ion battery copper foil surface treatment process, and propose a water-free, chromium-free antioxidant liquid for lithium ion battery copper foil and a preparation method and a use method.

[0007] To achieve the above object, the present invention is implemented through the following technical solutions:

[0008] A water-free, chromium-free antioxidant liquid for lithium-ion battery copper foil comprises the following components: 0.1-10 g / L of a corrosion inhibitor, 0.1-10 g / L of a film-forming aid, 0.1-10 mL / L of a sealant and 0.1-10 mL / L of a dispersant, and the remaining component is deionized water. Sodium hydroxide and formic acid are used to adjust the pH value of the solution to 4-6, and deionized water is used to adjust the volume to obtain a water-free, chromium-free antioxidant liquid for lithium-ion battery copper foil.

[0009] Furthermore, the corrosion inhibitor is one of 3-amino-5-mercapto-1,2,4-triazole, 2-mercaptobenzothiazole, 2-aminobenzothiazole, 5-aminotetrazolyl, 1-methyl-5-mercaptotetrazolyl, 1-phenyl-5-mercaptotetrazolyl, sodium tungstate, sodium silicate, and lanthanum nitrate, or a mixture of two or more thereof.

[0010] Furthermore, the film-forming aid is one of polyacrylic acid, polymaleic acid, polyaspartic acid and maleic acid-acrylic acid copolymer.

[0011] Furthermore, the sealing agent is one of silicate compounds, and the molecular structure of the silicate compound is Si(OR1) x (OR2) 4-x , wherein R1 is methyl, R2 is ethyl, and the value range of x is 0-4.

[0012] Furthermore, the silicate compound is obtained by esterification reaction of tetrachlorosilane and a mixed solution of methanol and ethanol, wherein the volume ratio of the mixed solution of tetrachlorosilane to methanol and ethanol is 1:5. During the reaction, the mixed solution of tetrachlorosilane, methanol and ethanol is slowly added into a three-necked flask and stirred for 2-2.5 hours. After the reaction is completed, a separatory funnel is used to separate the organic phase and the aqueous phase, and the product at 150-160° C. is collected by distillation to obtain the silicate compound.

[0013] Furthermore, the dispersant is a mixture of 2,4-dimethyl-2,4-pentanediol and isopropanol, and the mass ratio of 2,4-dimethyl-2,4-pentanediol to isopropanol is 1:1.

[0014] Furthermore, the water-free, chromium-free antioxidant solution for lithium-ion battery copper foil comprises the following ingredients: 0.5-5 g / L of corrosion inhibitor, 1-4 g / L of film-forming aid, 1-4 mL / L of sealing agent, 1-3 mL / L of dispersant, and the rest is deionized water.

[0015] A method for preparing a water-free, chromium-free antioxidant solution for lithium-ion battery copper foil comprises the following steps:

[0016] S1. Prepare a tetrachlorosilane solution and a mixed solution of methanol and ethanol respectively, wherein the volume ratio of the tetrachlorosilane solution to the mixed solution of methanol and ethanol is 1:5;

[0017] S2. First add tetrachlorosilane solution into a three-necked flask, then slowly add the mixed solution of methanol and ethanol into the three-necked flask and keep stirring for 2-2.5 hours;

[0018] S3. After the reaction is completed, separate the organic phase and the aqueous phase using a separatory funnel, collect the product at 150° C.-160° C. by distillation, and obtain the blocking agent for standby use;

[0019] S4. Weigh a certain mass of sealant, corrosion inhibitor, film-forming aid, and dispersant according to the proportion of the components;

[0020] S5. Add a certain amount of deionized water into the container, add the sealing agent under uniform stirring, and stir until it is completely dissolved to obtain a first solution;

[0021] S6, adding a dispersant to the first solution and stirring evenly to obtain a second solution;

[0022] S7, adding a corrosion inhibitor to the second solution and stirring for 1-2 hours until the corrosion inhibitor is completely dissolved to obtain a third solution;

[0023] S8. Add a film-forming aid to the third solution and stir for 20-30 minutes until the solution is uniform, then use sodium hydroxide and formic acid to adjust the pH value of the solution to 4-6, and stir evenly, and finally use deionized water to make up the volume to obtain a water-free, chromium-free antioxidant solution for lithium-ion battery copper foil.

[0024] Furthermore, in step S1, the volume ratio of methanol to ethanol in the mixed solution of methanol:ethanol is 1:0 or 0:1 or 1:1 or 1:3 or 3:1.

[0025] A method for using a water-free chromium-free antioxidant liquid for lithium-ion battery copper foil, wherein the lithium-ion battery copper foil is placed in the water-free chromium-free antioxidant liquid for lithium-ion battery copper foil for antioxidant treatment, the treatment temperature is 20-50°C, the treatment time is 10-90s, and the foil is taken out and naturally dried or blown dry.

[0026] Beneficial effects of the present invention:

[0027] The water-free, chromium-free antioxidant liquid for lithium-ion battery copper foil of the present invention is composed of a corrosion inhibitor, a film-forming aid, a sealing agent and a dispersant. The film-forming aid is adsorbed on the surface of the copper foil as the skeleton of the protective film, and then the corrosion inhibitor is selectively filled in the skeleton formed by the film-forming aid, and the sealing agent composed of silicate compounds is filled into the gap of the corrosion inhibitor adsorption film to avoid the invasion of oxygen or other corrosive media. Under the synergistic effect of several components, a uniform and dense protective film can be formed on the surface of the copper foil, which significantly improves its antioxidant and corrosion resistance in harsh environments, and does not affect the wettability and conductivity of the copper foil.

[0028] The water-free, chromium-free antioxidant liquid for lithium-ion battery copper foil of the present invention forms a uniform adsorption film on the surface of the copper foil by immersion. Under the action of a silicate compound and a dispersant, the water film on the surface of the copper foil can be quickly blown dry without leaving any water marks. Therefore, the copper foil treated with the antioxidant liquid does not need to go through a water washing step, and can be directly squeezed and dried. The process is simple, which saves water resources and solves the problems of complex traditional electrochemical passivation process and uneven passivation film. At the same time, the antioxidant liquid does not contain hexavalent chromium ions, and no chromium-containing wastewater is generated during the production process, which reduces the cost of enterprise wastewater treatment. The antioxidant liquid is green and environmentally friendly.

[0029] The water-free, chromium-free antioxidant liquid for lithium-ion battery copper foil of the present invention can obtain a passivation film with excellent antioxidant and corrosion resistance on the surface of the copper foil for lithium-ion batteries, and can protect the copper foil from discoloration when baked at 140°C for 15 minutes. At the same time, the conductivity and wettability of the copper foil are not affected after passivation, thus meeting the requirements of lithium-ion battery copper foil.

[0030] The water-free, chromium-free antioxidant liquid for lithium-ion battery copper foil of the present invention has the advantages of being environmentally friendly, green and non-toxic, having good stability and low cost, and can ensure its passivation effect even after long-term cyclic use, and is very suitable for application in industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a comparison chart of the effects of using the water-free, chromium-free antioxidant liquid for lithium-ion battery copper foil described in the present invention. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solution and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention, that is, the specific embodiments described are only part of the embodiments of the present invention, rather than all of the specific embodiments. The components of the specific embodiments of the present invention described and shown in the drawings herein can be arranged and designed in various different configurations, and the present invention can also have other embodiments.

[0033] Therefore, the following detailed description of the specific embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents the selected specific embodiments of the present invention. Based on the specific embodiments of the present invention, all other specific embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present invention.

[0034] In order to further understand the content, features and effects of the present invention, the following specific implementation methods are given as examples, and the attached Figure 1 The detailed instructions are as follows:

[0035] Embodiment 1:

[0036] A water-free, chromium-free antioxidant liquid for lithium-ion battery copper foil comprises the following components: 4 g / L of a corrosion inhibitor, 3.5 g / L of a film-forming aid, 2.5 mL / L of a sealant and 1.5 mL / L of a dispersant, and the remaining component is deionized water. Sodium hydroxide and formic acid are used to adjust the pH value of the solution to 4-6, and deionized water is used to adjust the volume to obtain a water-free, chromium-free antioxidant liquid for lithium-ion battery copper foil.

[0037] Furthermore, the corrosion inhibitor is a mixture of 3-amino-5-mercapto-1,2,4-triazole and 2-mercaptobenzothiazole, wherein the content of 3-amino-5-mercapto-1,2,4-triazole is 1.5 g / L and the content of 2-mercaptobenzothiazole is 2.5 g / L.

[0038] Furthermore, the film-forming aid is polyacrylic acid.

[0039] Furthermore, the sealing agent is one of silicate compounds, and the molecular structure of the silicate compound is Si(OR1) x (OR2) 4-x , wherein R1 is methyl, R2 is ethyl, and the value range of x is 0-4.

[0040] Furthermore, the silicate compound is obtained by esterification reaction of tetrachlorosilane and a mixed solution of methanol and ethanol, wherein the volume ratio of the mixed solution of tetrachlorosilane to methanol and ethanol is 1:5. During the reaction, the mixed solution of tetrachlorosilane, methanol and ethanol is slowly added into a three-necked flask and stirred for 2 hours. After the reaction is completed, a separatory funnel is used to separate the organic phase and the aqueous phase, and the product at 150-160° C. is collected by distillation to obtain the silicate compound.

[0041] Furthermore, the dispersant is a mixture of 2,4-dimethyl-2,4-pentanediol and isopropanol, and the mass ratio of 2,4-dimethyl-2,4-pentanediol to isopropanol is 1:1.

[0042] The method for preparing a water-free, chromium-free antioxidant solution for lithium-ion battery copper foil described in this embodiment comprises the following steps:

[0043] S1. Prepare a tetrachlorosilane solution and a mixed solution of methanol and ethanol respectively, wherein the volume ratio of the tetrachlorosilane solution to the mixed solution of methanol and ethanol is 1:5;

[0044] S2. First add tetrachlorosilane solution into a three-necked flask, then slowly add the mixed solution of methanol and ethanol into the three-necked flask and keep stirring for 2 hours;

[0045] S3. After the reaction is completed, separate the organic phase and the aqueous phase using a separatory funnel, collect the product at 150° C.-160° C. by distillation, and obtain the blocking agent for standby use;

[0046] S4. Weigh a certain mass of sealant, corrosion inhibitor, film-forming aid, and dispersant according to the proportion of the components;

[0047] S5. Add a certain amount of deionized water into the container, add the sealing agent under uniform stirring, and stir until it is completely dissolved to obtain a first solution;

[0048] S6, adding a dispersant to the first solution and stirring evenly to obtain a second solution;

[0049] S7, adding a corrosion inhibitor to the second solution and stirring for 1.5 hours until the corrosion inhibitor is completely dissolved to obtain a third solution;

[0050] S8. Add a film-forming aid to the third solution and stir for 20 minutes until the solution is uniform, then use sodium hydroxide and formic acid to adjust the pH value of the solution to 4-6, and stir evenly, and finally use deionized water to make up the volume to obtain a water-free, chromium-free antioxidant solution for lithium-ion battery copper foil.

[0051] Furthermore, in step S1, the mixed solution of methanol and ethanol has a volume ratio of methanol:ethanol of 1:0.

[0052] Embodiment 2:

[0053] A water-free, chromium-free antioxidant liquid for lithium-ion battery copper foil comprises the following components: 4 g / L of a corrosion inhibitor, 3.5 g / L of a film-forming aid, 2.5 mL / L of a sealant and 1.5 mL / L of a dispersant, and the remaining component is deionized water. Sodium hydroxide and formic acid are used to adjust the pH value of the solution to 4-6, and deionized water is used to adjust the volume to obtain a water-free, chromium-free antioxidant liquid for lithium-ion battery copper foil.

[0054] Furthermore, the corrosion inhibitor is a mixture of 2-aminobenzothiazole and 5-aminotetrazole, wherein the 2-aminobenzothiazole is 1.5 g / L and the 5-aminotetrazole is 2.5 g / L.

[0055] Furthermore, the film-forming aid is polymaleic acid.

[0056] Furthermore, the sealing agent is one of silicate compounds, and the molecular structure of the silicate compound is Si(OR1) x (OR2) 4-x, wherein R1 is methyl, R2 is ethyl, and the value range of x is 0-4.

[0057] Furthermore, the silicate compound is obtained by esterification reaction of tetrachlorosilane and a mixed solution of methanol and ethanol, wherein the volume ratio of the mixed solution of tetrachlorosilane to methanol and ethanol is 1:5. During the reaction, the mixed solution of tetrachlorosilane, methanol and ethanol is slowly added into a three-necked flask and stirred for 2 hours. After the reaction is completed, a separatory funnel is used to separate the organic phase and the aqueous phase, and the product at 150-160° C. is collected by distillation to obtain the silicate compound.

[0058] Furthermore, the dispersant is a mixture of 2,4-dimethyl-2,4-pentanediol and isopropanol, and the mass ratio of 2,4-dimethyl-2,4-pentanediol to isopropanol is 1:1.

[0059] The method for preparing a water-free, chromium-free antioxidant solution for lithium-ion battery copper foil described in this embodiment comprises the following steps:

[0060] S1. Prepare a tetrachlorosilane solution and a mixed solution of methanol and ethanol respectively, wherein the volume ratio of the tetrachlorosilane solution to the mixed solution of methanol and ethanol is 1:5;

[0061] S2. First add tetrachlorosilane solution into a three-necked flask, then slowly add the mixed solution of methanol and ethanol into the three-necked flask and keep stirring for 2 hours;

[0062] S3. After the reaction is completed, separate the organic phase and the aqueous phase using a separatory funnel, collect the product at 150° C.-160° C. by distillation, and obtain the blocking agent for standby use;

[0063] S4. Weigh a certain mass of sealant, corrosion inhibitor, film-forming aid, and dispersant according to the proportion of the components;

[0064] S5. Add a certain amount of deionized water into the container, add the sealing agent under uniform stirring, and stir until it is completely dissolved to obtain a first solution;

[0065] S6, adding a dispersant to the first solution and stirring evenly to obtain a second solution;

[0066] S7, adding a corrosion inhibitor to the second solution and stirring for 1.5 hours until the corrosion inhibitor is completely dissolved to obtain a third solution;

[0067] S8. Add a film-forming aid to the third solution and stir for 20 minutes until the solution is uniform, then use sodium hydroxide and formic acid to adjust the pH value of the solution to 4-6, and stir evenly, and finally use deionized water to make up the volume to obtain a water-free, chromium-free antioxidant solution for lithium-ion battery copper foil.

[0068] Furthermore, in step S1, the volume ratio of methanol to ethanol in the mixed solution of methanol to ethanol is 0:1.

[0069] Embodiment 3:

[0070] A water-free, chromium-free antioxidant liquid for lithium-ion battery copper foil comprises the following components: 4 g / L of a corrosion inhibitor, 3.5 g / L of a film-forming aid, 2.5 mL / L of a sealant and 1.5 mL / L of a dispersant, and the remaining component is deionized water. Sodium hydroxide and formic acid are used to adjust the pH value of the solution to 4-6, and deionized water is used to adjust the volume to obtain a water-free, chromium-free antioxidant liquid for lithium-ion battery copper foil.

[0071] Furthermore, the corrosion inhibitor is a mixture of 1-methyl-5-mercaptotetrazole and 1-phenyl-5-mercaptotetrazole, wherein the content of 1-methyl-5-mercaptotetrazole is 1.5 g / L and the content of 1-phenyl-5-mercaptotetrazole is 2.5 g / L.

[0072] Furthermore, the film-forming aid is polyaspartic acid.

[0073] Furthermore, the sealing agent is one of silicate compounds, and the molecular structure of the silicate compound is Si(OR1) x (OR2) 4-x , wherein R1 is methyl, R2 is ethyl, and the value range of x is 0-4.

[0074] Furthermore, the silicate compound is obtained by esterification reaction of tetrachlorosilane and a mixed solution of methanol and ethanol, wherein the volume ratio of the mixed solution of tetrachlorosilane to methanol and ethanol is 1:5. During the reaction, the mixed solution of tetrachlorosilane, methanol and ethanol is slowly added into a three-necked flask and stirred for 2 hours. After the reaction is completed, a separatory funnel is used to separate the organic phase and the aqueous phase, and the product at 150-160° C. is collected by distillation to obtain the silicate compound.

[0075] Furthermore, the dispersant is a mixture of 2,4-dimethyl-2,4-pentanediol and isopropanol, and the mass ratio of 2,4-dimethyl-2,4-pentanediol to isopropanol is 1:1.

[0076] The method for preparing a water-free, chromium-free antioxidant solution for lithium-ion battery copper foil described in this embodiment comprises the following steps:

[0077] S1. Prepare a tetrachlorosilane solution and a mixed solution of methanol and ethanol respectively, wherein the volume ratio of the tetrachlorosilane solution to the mixed solution of methanol and ethanol is 1:5;

[0078] S2. First add tetrachlorosilane solution into a three-necked flask, then slowly add the mixed solution of methanol and ethanol into the three-necked flask and keep stirring for 2 hours;

[0079] S3. After the reaction is completed, separate the organic phase and the aqueous phase using a separatory funnel, collect the product at 150° C.-160° C. by distillation, and obtain the blocking agent for standby use;

[0080] S4. Weigh a certain mass of sealant, corrosion inhibitor, film-forming aid, and dispersant according to the proportion of the components;

[0081] S5. Add a certain amount of deionized water into the container, add the sealing agent under uniform stirring, and stir until it is completely dissolved to obtain a first solution;

[0082] S6, adding a dispersant to the first solution and stirring evenly to obtain a second solution;

[0083] S7, adding a corrosion inhibitor to the second solution and stirring for 1.5 hours until the corrosion inhibitor is completely dissolved to obtain a third solution;

[0084] S8. Add a film-forming aid to the third solution and stir for 20 minutes until the solution is uniform, then use sodium hydroxide and formic acid to adjust the pH value of the solution to 4-6, and stir evenly, and finally use deionized water to make up the volume to obtain a water-free, chromium-free antioxidant solution for lithium-ion battery copper foil.

[0085] Furthermore, in step S1, the volume ratio of methanol to ethanol in the mixed solution of methanol:ethanol is 1:1.

[0086] Embodiment 4:

[0087] A water-free, chromium-free antioxidant liquid for lithium-ion battery copper foil comprises the following components: 4 g / L of a corrosion inhibitor, 3.5 g / L of a film-forming aid, 2.5 mL / L of a sealant and 1.5 mL / L of a dispersant, and the remaining component is deionized water. Sodium hydroxide and formic acid are used to adjust the pH value of the solution to 4-6, and deionized water is used to adjust the volume to obtain a water-free, chromium-free antioxidant liquid for lithium-ion battery copper foil.

[0088] Furthermore, the corrosion inhibitor is a mixture of 5-aminotetrazole and sodium tungstate, wherein the 5-aminotetrazole is 1.5 g / L and the sodium tungstate is 2.5 g / L.

[0089] Furthermore, the film-forming aid is a maleic acid-acrylic acid copolymer.

[0090] Furthermore, the sealing agent is one of silicate compounds, and the molecular structure of the silicate compound is Si(OR1) x (OR2) 4-x , wherein R1 is methyl, R2 is ethyl, and the value range of x is 0-4.

[0091] Furthermore, the silicate compound is obtained by esterification reaction of tetrachlorosilane and a mixed solution of methanol and ethanol, wherein the volume ratio of the mixed solution of tetrachlorosilane to methanol and ethanol is 1:5. During the reaction, the mixed solution of tetrachlorosilane, methanol and ethanol is slowly added into a three-necked flask and stirred for 2 hours. After the reaction is completed, a separatory funnel is used to separate the organic phase and the aqueous phase, and the product at 150-160° C. is collected by distillation to obtain the silicate compound.

[0092] Furthermore, the dispersant is a mixture of 2,4-dimethyl-2,4-pentanediol and isopropanol, and the mass ratio of 2,4-dimethyl-2,4-pentanediol to isopropanol is 1:1.

[0093] The method for preparing a water-free, chromium-free antioxidant solution for lithium-ion battery copper foil described in this embodiment comprises the following steps:

[0094] S1. Prepare a tetrachlorosilane solution and a mixed solution of methanol and ethanol respectively, wherein the volume ratio of the tetrachlorosilane solution to the mixed solution of methanol and ethanol is 1:5;

[0095] S2. First add tetrachlorosilane solution into a three-necked flask, then slowly add the mixed solution of methanol and ethanol into the three-necked flask and keep stirring for 2 hours;

[0096] S3. After the reaction is completed, separate the organic phase and the aqueous phase using a separatory funnel, collect the product at 150° C.-160° C. by distillation, and obtain the blocking agent for standby use;

[0097] S4. Weigh a certain mass of sealant, corrosion inhibitor, film-forming aid, and dispersant according to the proportion of the components;

[0098] S5. Add a certain amount of deionized water into the container, add the sealing agent under uniform stirring, and stir until it is completely dissolved to obtain a first solution;

[0099] S6, adding a dispersant to the first solution and stirring evenly to obtain a second solution;

[0100] S7, adding a corrosion inhibitor to the second solution and stirring for 1.5 hours until the corrosion inhibitor is completely dissolved to obtain a third solution;

[0101] S8. Add a film-forming aid to the third solution and stir for 20 minutes until the solution is uniform, then use sodium hydroxide and formic acid to adjust the pH value of the solution to 4-6, and stir evenly, and finally use deionized water to make up the volume to obtain a water-free, chromium-free antioxidant solution for lithium-ion battery copper foil.

[0102] Furthermore, in step S1, the volume ratio of methanol to ethanol in the mixed solution of methanol:ethanol is 3:1.

[0103] Embodiment 5:

[0104] A water-free, chromium-free antioxidant liquid for lithium-ion battery copper foil comprises the following components: 4 g / L of a corrosion inhibitor, 2.5 g / L of a film-forming aid, 2.5 mL / L of a sealing agent and 1.5 mL / L of a dispersant, and the remaining component is deionized water. Then, sodium hydroxide and formic acid are used to adjust the pH value of the solution to 4-6, and deionized water is used to adjust the volume to obtain a water-free, chromium-free antioxidant liquid for lithium-ion battery copper foil.

[0105] Furthermore, the corrosion inhibitor is a mixture of 1-methyl-5-mercaptotetrazole and sodium silicate, wherein the 1-methyl-5-mercaptotetrazole is 1.5 g / L and the sodium silicate is 2.5 g / L.

[0106] Furthermore, the film-forming aid is polyacrylic acid.

[0107] Furthermore, the sealing agent is one of silicate compounds, and the molecular structure of the silicate compound is Si(OR1) x (OR2) 4-x , wherein R1 is methyl, R2 is ethyl, and the value range of x is 0-4.

[0108] Furthermore, the silicate compound is obtained by esterification reaction of tetrachlorosilane and a mixed solution of methanol and ethanol, wherein the volume ratio of the mixed solution of tetrachlorosilane to methanol and ethanol is 1:5. During the reaction, the mixed solution of tetrachlorosilane, methanol and ethanol is slowly added into a three-necked flask and stirred for 2 hours. After the reaction is completed, a separatory funnel is used to separate the organic phase and the aqueous phase, and the product at 150-160° C. is collected by distillation to obtain the silicate compound.

[0109] Furthermore, the dispersant is a mixture of 2,4-dimethyl-2,4-pentanediol and isopropanol, and the mass ratio of 2,4-dimethyl-2,4-pentanediol to isopropanol is 1:1.

[0110] The method for preparing a water-free, chromium-free antioxidant solution for lithium-ion battery copper foil described in this embodiment comprises the following steps:

[0111] S1. Prepare a tetrachlorosilane solution and a mixed solution of methanol and ethanol respectively, wherein the volume ratio of the tetrachlorosilane solution to the mixed solution of methanol and ethanol is 1:5;

[0112] S2. First add tetrachlorosilane solution into a three-necked flask, then slowly add the mixed solution of methanol and ethanol into the three-necked flask and keep stirring for 2 hours;

[0113] S3. After the reaction is completed, separate the organic phase and the aqueous phase using a separatory funnel, collect the product at 150° C.-160° C. by distillation, and obtain the blocking agent for standby use;

[0114] S4. Weigh a certain mass of sealant, corrosion inhibitor, film-forming aid, and dispersant according to the proportion of the components;

[0115] S5. Add a certain amount of deionized water into the container, add the sealing agent under uniform stirring, and stir until it is completely dissolved to obtain a first solution;

[0116] S6, adding a dispersant to the first solution and stirring evenly to obtain a second solution;

[0117] S7, adding a corrosion inhibitor to the second solution and stirring for 1.5 hours until the corrosion inhibitor is completely dissolved to obtain a third solution;

[0118] S8. Add a film-forming aid to the third solution and stir for 20 minutes until the solution is uniform, then use sodium hydroxide and formic acid to adjust the pH value of the solution to 4-6, and stir evenly, and finally use deionized water to make up the volume to obtain a water-free, chromium-free antioxidant solution for lithium-ion battery copper foil.

[0119] Furthermore, in step S1, the volume ratio of methanol to ethanol in the mixed solution of methanol:ethanol is 1:3.

[0120] Embodiment 6:

[0121] A water-free, chromium-free antioxidant liquid for lithium-ion battery copper foil comprises the following components: 4 g / L of a corrosion inhibitor, 2.5 g / L of a film-forming aid, 2.5 mL / L of a sealing agent and 1.5 mL / L of a dispersant, and the remaining component is deionized water. Then, sodium hydroxide and formic acid are used to adjust the pH value of the solution to 4-6, and deionized water is used to adjust the volume to obtain a water-free, chromium-free antioxidant liquid for lithium-ion battery copper foil.

[0122] Furthermore, the corrosion inhibitor is a mixture of lanthanum nitrate and 5-aminotetrazole, wherein the lanthanum nitrate is 1.5 g / L and the 5-aminotetrazole is 2.5 g / L.

[0123] Furthermore, the film-forming aid is a maleic acid-acrylic acid copolymer.

[0124] Furthermore, the sealing agent is one of silicate compounds, and the molecular structure of the silicate compound is Si(OR1) x (OR2) 4-x , wherein R1 is methyl, R2 is ethyl, and the value range of x is 0-4.

[0125] Furthermore, the silicate compound is obtained by esterification reaction of tetrachlorosilane and a mixed solution of methanol and ethanol, wherein the volume ratio of the mixed solution of tetrachlorosilane to methanol and ethanol is 1:5. During the reaction, the mixed solution of tetrachlorosilane, methanol and ethanol is slowly added into a three-necked flask and stirred for 2 hours. After the reaction is completed, a separatory funnel is used to separate the organic phase and the aqueous phase, and the product at 150-160° C. is collected by distillation to obtain the silicate compound.

[0126] Furthermore, the dispersant is a mixture of 2,4-dimethyl-2,4-pentanediol and isopropanol, and the mass ratio of 2,4-dimethyl-2,4-pentanediol to isopropanol is 1:1.

[0127] The method for preparing a water-free, chromium-free antioxidant solution for lithium-ion battery copper foil described in this embodiment comprises the following steps:

[0128] S1. Prepare a tetrachlorosilane solution and a mixed solution of methanol and ethanol respectively, wherein the volume ratio of the tetrachlorosilane solution to the mixed solution of methanol and ethanol is 1:5;

[0129] S2. First add tetrachlorosilane solution into a three-necked flask, then slowly add the mixed solution of methanol and ethanol into the three-necked flask and keep stirring for 2 hours;

[0130] S3. After the reaction is completed, separate the organic phase and the aqueous phase using a separatory funnel, collect the product at 150° C.-160° C. by distillation, and obtain the blocking agent for standby use;

[0131] S4. Weigh a certain mass of sealant, corrosion inhibitor, film-forming aid, and dispersant according to the proportion of the components;

[0132] S5. Add a certain amount of deionized water into the container, add the sealing agent under uniform stirring, and stir until it is completely dissolved to obtain a first solution;

[0133] S6, adding a dispersant to the first solution and stirring evenly to obtain a second solution;

[0134] S7, adding a corrosion inhibitor to the second solution and stirring for 1.5 hours until the corrosion inhibitor is completely dissolved to obtain a third solution;

[0135] S8. Add a film-forming aid to the third solution and stir for 20 minutes until the solution is uniform, then use sodium hydroxide and formic acid to adjust the pH value of the solution to 4-6, and stir evenly, and finally use deionized water to make up the volume to obtain a water-free, chromium-free antioxidant solution for lithium-ion battery copper foil.

[0136] Furthermore, in step S1, the volume ratio of methanol to ethanol in the mixed solution of methanol:ethanol is 1:3.

[0137] Embodiment 7:

[0138] A water-free, chromium-free antioxidant liquid for lithium-ion battery copper foil comprises the following components: 3 g / L of a corrosion inhibitor, 2.5 g / L of a film-forming aid, 2.5 mL / L of a sealing agent and 1.5 mL / L of a dispersant, and the remaining component is deionized water. Then, sodium hydroxide and formic acid are used to adjust the pH value of the solution to 4-6, and deionized water is used to adjust the volume to obtain a water-free, chromium-free antioxidant liquid for lithium-ion battery copper foil.

[0139] Furthermore, the corrosion inhibitor is a mixture of 1-methyl-5-mercaptotetrazole and 1-phenyl-5-mercaptotetrazole, wherein the content of 1-methyl-5-mercaptotetrazole is 1.5 g / L and the content of 1-phenyl-5-mercaptotetrazole is 1.5 g / L.

[0140] Furthermore, the film-forming aid is a maleic acid-acrylic acid copolymer.

[0141] Furthermore, the sealing agent is one of silicate compounds, and the molecular structure of the silicate compound is Si(OR1) x (OR2) 4-x , wherein R1 is methyl, R2 is ethyl, and the value range of x is 0-4.

[0142] Furthermore, the silicate compound is obtained by esterification reaction of tetrachlorosilane and a mixed solution of methanol and ethanol, wherein the volume ratio of the mixed solution of tetrachlorosilane to methanol and ethanol is 1:5. During the reaction, the mixed solution of tetrachlorosilane, methanol and ethanol is slowly added into a three-necked flask and stirred for 2 hours. After the reaction is completed, a separatory funnel is used to separate the organic phase and the aqueous phase, and the product at 150-160° C. is collected by distillation to obtain the silicate compound.

[0143] Furthermore, the dispersant is a mixture of 2,4-dimethyl-2,4-pentanediol and isopropanol, and the mass ratio of 2,4-dimethyl-2,4-pentanediol to isopropanol is 1:1.

[0144] The method for preparing a water-free, chromium-free antioxidant solution for lithium-ion battery copper foil described in this embodiment comprises the following steps:

[0145] S1. Prepare a tetrachlorosilane solution and a mixed solution of methanol and ethanol respectively, wherein the volume ratio of the tetrachlorosilane solution to the mixed solution of methanol and ethanol is 1:5;

[0146] S2. First add tetrachlorosilane solution into a three-necked flask, then slowly add the mixed solution of methanol and ethanol into the three-necked flask and keep stirring for 2 hours;

[0147] S3. After the reaction is completed, separate the organic phase and the aqueous phase using a separatory funnel, collect the product at 150° C.-160° C. by distillation, and obtain the blocking agent for standby use;

[0148] S4. Weigh a certain mass of sealant, corrosion inhibitor, film-forming aid, and dispersant according to the proportion of the components;

[0149] S5. Add a certain amount of deionized water into the container, add the sealing agent under uniform stirring, and stir until it is completely dissolved to obtain a first solution;

[0150] S6, adding a dispersant to the first solution and stirring evenly to obtain a second solution;

[0151] S7, adding a corrosion inhibitor to the second solution and stirring for 1.5 hours until the corrosion inhibitor is completely dissolved to obtain a third solution;

[0152] S8. Add a film-forming aid to the third solution and stir for 20 minutes until the solution is uniform, then use sodium hydroxide and formic acid to adjust the pH value of the solution to 4-6, and stir evenly, and finally use deionized water to make up the volume to obtain a water-free, chromium-free antioxidant solution for lithium-ion battery copper foil.

[0153] Furthermore, in step S1, the volume ratio of methanol to ethanol in the mixed solution of methanol:ethanol is 1:1.

[0154] Embodiment 8:

[0155] A water-free, chromium-free antioxidant liquid for lithium-ion battery copper foil comprises the following components: 3 g / L of a corrosion inhibitor, 2.5 g / L of a film-forming aid, 2.5 mL / L of a sealing agent and 1.5 mL / L of a dispersant, and the remaining component is deionized water. Then, sodium hydroxide and formic acid are used to adjust the pH value of the solution to 4-6, and deionized water is used to adjust the volume to obtain a water-free, chromium-free antioxidant liquid for lithium-ion battery copper foil.

[0156] Furthermore, the corrosion inhibitor is a mixture of 1-methyl-5-mercaptotetrazole and sodium silicate, wherein the 1-methyl-5-mercaptotetrazole is 1.5 g / L and the sodium silicate is 1.5 g / L.

[0157] Furthermore, the film-forming aid is a maleic acid-acrylic acid copolymer.

[0158] Furthermore, the sealing agent is one of silicate compounds, and the molecular structure of the silicate compound is Si(OR1) x (OR2) 4-x , wherein R1 is methyl, R2 is ethyl, and the value range of x is 0-4.

[0159] Furthermore, the silicate compound is obtained by esterification reaction of tetrachlorosilane and a mixed solution of methanol and ethanol, wherein the volume ratio of the mixed solution of tetrachlorosilane to methanol and ethanol is 1:5. During the reaction, the mixed solution of tetrachlorosilane, methanol and ethanol is slowly added into a three-necked flask and stirred for 2 hours. After the reaction is completed, a separatory funnel is used to separate the organic phase and the aqueous phase, and the product at 150-160° C. is collected by distillation to obtain the silicate compound.

[0160] Furthermore, the dispersant is a mixture of 2,4-dimethyl-2,4-pentanediol and isopropanol, and the mass ratio of 2,4-dimethyl-2,4-pentanediol to isopropanol is 1:1.

[0161] The method for preparing a water-free, chromium-free antioxidant solution for lithium-ion battery copper foil described in this embodiment comprises the following steps:

[0162] S1. Prepare a tetrachlorosilane solution and a mixed solution of methanol and ethanol respectively, wherein the volume ratio of the tetrachlorosilane solution to the mixed solution of methanol and ethanol is 1:5;

[0163] S2. First add tetrachlorosilane solution into a three-necked flask, then slowly add the mixed solution of methanol and ethanol into the three-necked flask and keep stirring for 2 hours;

[0164] S3. After the reaction is completed, separate the organic phase and the aqueous phase using a separatory funnel, collect the product at 150° C.-160° C. by distillation, and obtain the blocking agent for standby use;

[0165] S4. Weigh a certain mass of sealant, corrosion inhibitor, film-forming aid, and dispersant according to the proportion of the components;

[0166] S5. Add a certain amount of deionized water into the container, add the sealing agent under uniform stirring, and stir until it is completely dissolved to obtain a first solution;

[0167] S6, adding a dispersant to the first solution and stirring evenly to obtain a second solution;

[0168] S7, adding a corrosion inhibitor to the second solution and stirring for 1.5 hours until the corrosion inhibitor is completely dissolved to obtain a third solution;

[0169] S8. Add a film-forming aid to the third solution and stir for 20 minutes until the solution is uniform, then use sodium hydroxide and formic acid to adjust the pH value of the solution to 4-6, and stir evenly, and finally use deionized water to make up the volume to obtain a water-free, chromium-free antioxidant solution for lithium-ion battery copper foil.

[0170] Furthermore, in step S1, the volume ratio of methanol to ethanol in the mixed solution of methanol:ethanol is 1:1.

[0171] Embodiment 9:

[0172] A water-free, chromium-free antioxidant liquid for lithium-ion battery copper foil comprises the following components: 3 g / L of a corrosion inhibitor, 2.5 g / L of a film-forming aid, 2.5 mL / L of a sealing agent and 1.5 mL / L of a dispersant, and the remaining component is deionized water. Then, sodium hydroxide and formic acid are used to adjust the pH value of the solution to 4-6, and deionized water is used to adjust the volume to obtain a water-free, chromium-free antioxidant liquid for lithium-ion battery copper foil.

[0173] Furthermore, the corrosion inhibitor is a mixture of 5-aminotetrazole and sodium tungstate, wherein the 5-aminotetrazole is 1.5 g / L and the sodium tungstate is 1.5 g / L.

[0174] Furthermore, the film-forming aid is a maleic acid-acrylic acid copolymer.

[0175] Furthermore, the sealing agent is one of silicate compounds, and the molecular structure of the silicate compound is Si(OR1) x (OR2) 4-x , wherein R1 is methyl, R2 is ethyl, and the value range of x is 0-4.

[0176] Furthermore, the silicate compound is obtained by esterification reaction of tetrachlorosilane and a mixed solution of methanol and ethanol, wherein the volume ratio of the mixed solution of tetrachlorosilane to methanol and ethanol is 1:5. During the reaction, the mixed solution of tetrachlorosilane, methanol and ethanol is slowly added into a three-necked flask and stirred for 2 hours. After the reaction is completed, a separatory funnel is used to separate the organic phase and the aqueous phase, and the product at 150-160° C. is collected by distillation to obtain the silicate compound.

[0177] Furthermore, the dispersant is a mixture of 2,4-dimethyl-2,4-pentanediol and isopropanol, and the mass ratio of 2,4-dimethyl-2,4-pentanediol to isopropanol is 1:1.

[0178] The method for preparing a water-free, chromium-free antioxidant solution for lithium-ion battery copper foil described in this embodiment comprises the following steps:

[0179] S1. Prepare a tetrachlorosilane solution and a mixed solution of methanol and ethanol respectively, wherein the volume ratio of the tetrachlorosilane solution to the mixed solution of methanol and ethanol is 1:5;

[0180] S2. First add tetrachlorosilane solution into a three-necked flask, then slowly add the mixed solution of methanol and ethanol into the three-necked flask and keep stirring for 2 hours;

[0181] S3. After the reaction is completed, separate the organic phase and the aqueous phase using a separatory funnel, collect the product at 150° C.-160° C. by distillation, and obtain the blocking agent for standby use;

[0182] S4. Weigh a certain mass of sealant, corrosion inhibitor, film-forming aid, and dispersant according to the proportion of the components;

[0183] S5. Add a certain amount of deionized water into the container, add the sealing agent under uniform stirring, and stir until it is completely dissolved to obtain a first solution;

[0184] S6, adding a dispersant to the first solution and stirring evenly to obtain a second solution;

[0185] S7, adding a corrosion inhibitor to the second solution and stirring for 1.5 hours until the corrosion inhibitor is completely dissolved to obtain a third solution;

[0186] S8. Add a film-forming aid to the third solution and stir for 20 minutes until the solution is uniform, then use sodium hydroxide and formic acid to adjust the pH value of the solution to 4-6, and stir evenly, and finally use deionized water to make up the volume to obtain a water-free, chromium-free antioxidant solution for lithium-ion battery copper foil.

[0187] Furthermore, in step S1, the volume ratio of methanol to ethanol in the mixed solution of methanol:ethanol is 1:1.

[0188] Comparative Example 1:

[0189] The difference between Comparative Example 1 and Example 9 is that no silicate compound is added in Comparative Example 1.

[0190] Comparative Example 2:

[0191] The difference between Comparative Example 2 and Example 9 is that no maleic acid acrylic acid copolymer is added in Comparative Example 2.

[0192] The following tests were performed on Examples 1 to 9 and Comparative Examples 1 and 2;

[0193] Antioxidation test: According to the national standard GB / T 36146-2018 and the industry standard SJ / T 11483-2014, after the copper foil for lithium-ion batteries is passivated and baked at 140°C for 15 minutes, there should be no oxidative discoloration or color spots on the surface of the copper foil.

[0194] Square resistance test: Use a four-probe square resistance meter to test the square resistance of the copper foil after anti-oxidation treatment. Measure the copper foil with a fixed side length of 2cm*2cm. Select three points on the same copper foil for testing, and take the average value of the three measurements for square resistance.

[0195] Wettability test: Use 36, 38 and 40 dyne pens to test the wettability of the copper foil after antioxidant treatment to observe whether the copper foil is wet after using the dyne pen.

[0196] The test results obtained are as follows Figure 1As shown in Table 1:

[0197] Table 1 Test results of surface properties of copper foil in embodiments and comparative examples

[0198] serial number Square resistance(Ω) Wettability Untreated samples 0.0186 36、38 Example 1 0.0175 36、38、40 Example 2 0.0197 36、38、40 Example 3 0.0199 36、38、40 Example 4 0.0187 36、38、40 Example 5 0.0177 36、38、40 Example 6 0.0167 36、38、40 Example 7 0.0195 36、38、40 Example 8 0.0164 36、38、40 Example 9 0.0174 36、38、40 Comparative Example 1 0.0212 36 Comparative Example 2 0.0188 36、38

[0199] From Table 1 and Figure 1 It can be seen from the test results that, compared with the untreated sample, Comparative Example 1 and Comparative Example 2, the surface color of the lithium ion battery copper foil prepared by using the water-free chromium-free antioxidant liquid for lithium ion battery copper foil of the present invention is uniform, which can ensure that 36, 38 and 40 dyne pens are all wetted, the conductive performance is equivalent to that before treatment, and the oxidation resistance is good. After baking at 140°C for 15 minutes, no oxidative discoloration occurs, which can meet the performance requirements and production needs of the composite copper foil for lithium ion batteries.

[0200] It should be noted that relational terms such as "first" and "second" are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0201] Although the present application has been described above with reference to specific embodiments, various modifications may be made thereto and parts thereof may be replaced with equivalents without departing from the scope of the present application. In particular, as long as there is no structural conflict, the various features in the specific embodiments disclosed in the present application may be used in combination with each other in any manner, and the fact that these combinations are not exhaustively described in this specification is only for the sake of omitting space and saving resources. Therefore, the present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.

Claims

1. A water-free, chromium-free antioxidant solution for lithium-ion battery copper foil, characterized in that: The invention comprises the following components: 0.1-10 g / L of corrosion inhibitor, 0.1-10 g / L of film-forming aid, 0.1-10 mL / L of sealing agent and 0.1-10 mL / L of dispersant, and the remaining components are deionized water. Then, sodium hydroxide and formic acid are used to adjust the pH value of the solution to 4-6, and deionized water is used to make the volume constant to obtain a water-free, chromium-free antioxidant liquid for lithium ion battery copper foil.

2. The water-free, chromium-free antioxidant solution for lithium-ion battery copper foil according to claim 1, characterized in that: The corrosion inhibitor is one of 3-amino-5-mercapto-1,2,4-triazole, 2-mercaptobenzothiazole, 2-aminobenzothiazole, 5-aminotetrazolyl, 1-methyl-5-mercaptotetrazolyl, 1-phenyl-5-mercaptotetrazolyl, sodium tungstate, sodium silicate and lanthanum nitrate, or a mixture of two or more thereof.

3. The water-free, chromium-free antioxidant solution for lithium-ion battery copper foil according to claim 1 or 2, characterized in that: The film-forming aid is one of polyacrylic acid, polymaleic acid, polyaspartic acid and maleic acid acrylic acid copolymer.

4. The water-free, chromium-free antioxidant solution for lithium-ion battery copper foil according to claim 3, characterized in that: The sealing agent is one of silicate compounds, and the molecular structure of the silicate compound is Si(OR1) x (OR2) 4-x , wherein R1 is methyl, R2 is ethyl, and the value range of x is 0-4.

5. The water-free, chromium-free antioxidant solution for lithium-ion battery copper foil according to claim 4, characterized in that: The silicate compound is obtained by esterification reaction of tetrachlorosilane and a mixed solution of methanol and ethanol, wherein the volume ratio of the mixed solution of tetrachlorosilane to methanol and ethanol is 1:

5. During the reaction, the mixed solution of tetrachlorosilane, methanol and ethanol is slowly added into a three-necked flask and stirred for 2-2.5 hours. After the reaction is completed, a separatory funnel is used to separate the organic phase and the aqueous phase, and the product at 150-160° C. is collected by distillation to obtain the silicate compound.

6. The water-free, chromium-free antioxidant solution for lithium-ion battery copper foil according to claim 5, characterized in that: The dispersant is a mixture of 2,4-dimethyl-2,4-pentanediol and isopropanol, and the mass ratio of 2,4-dimethyl-2,4-pentanediol to isopropanol is 1:

1.

7. The water-free, chromium-free antioxidant solution for lithium-ion battery copper foil according to claim 6, characterized in that: The water-free, chromium-free antioxidant solution for lithium-ion battery copper foil comprises the following components: 0.5-5 g / L of corrosion inhibitor, 1-4 g / L of film-forming aid, 1-4 mL / L of sealing agent, 1-3 mL / L of dispersant, and the rest is deionized water.

8. A method for preparing a water-free, chromium-free antioxidant solution for lithium-ion battery copper foil according to any one of claims 1 to 7, characterized in that: The steps include: S1. Prepare a tetrachlorosilane solution and a mixed solution of methanol and ethanol respectively, wherein the volume ratio of the tetrachlorosilane solution to the mixed solution of methanol and ethanol is 1:5; S2. First add tetrachlorosilane solution into a three-necked flask, then slowly add the mixed solution of methanol and ethanol into the three-necked flask and keep stirring for 2-2.5 hours; S3. After the reaction is completed, separate the organic phase and the aqueous phase using a separatory funnel, collect the product at 150° C.-160° C. by distillation, and obtain the blocking agent for standby use; S4. Weigh a certain mass of the sealant, corrosion inhibitor, film-forming aid, and dispersant according to the proportion of the components; S5. Add a certain amount of deionized water into the container, add the sealing agent under uniform stirring, and stir until it is completely dissolved to obtain a first solution; S6, adding a dispersant to the first solution and stirring evenly to obtain a second solution; S7, adding a corrosion inhibitor to the second solution and stirring for 1-2 hours until the corrosion inhibitor is completely dissolved to obtain a third solution; S8. Add a film-forming aid to the third solution and stir for 20-30 minutes until the solution is uniform, then use sodium hydroxide and formic acid to adjust the pH value of the solution to 4-6, and stir evenly, and finally use deionized water to make up the volume to obtain a water-free, chromium-free antioxidant solution for lithium-ion battery copper foil.

9. The method for preparing a water-free, chromium-free antioxidant solution for lithium-ion battery copper foil according to claim 8, characterized in that: In step S1, the volume ratio of methanol to ethanol in the mixed solution of methanol:ethanol is 1:0 or 0:1 or 1:1 or 1:3 or 3:

1.

10. A method for using the water-free, chromium-free antioxidant solution for lithium-ion battery copper foil according to any one of claims 1 to 7, characterized in that: The lithium-ion battery copper foil is placed in the water-free, chromium-free antioxidant solution for lithium-ion battery copper foil for antioxidant treatment at a treatment temperature of 20-50° C. for a treatment time of 10-90 seconds, and then taken out and naturally dried or blown dry.

Citation Information

Patent Citations

  • Special environment-friendly antioxidant additive for copper foil and preparation method thereof

    CN118727085A

  • Copper foil anti-oxidation surface treating agent as well as preparation method and use method thereof

    CN119082719A